An epidemiological study on knowledge, attitude and practice of injection safety among health care personnel in a tertiary care hospital of Tripura - Datta, Anjan; Nag, Kaushik; Karmakar, Nabarun; Chakraborty, Tamal (International Journal Of Community Medicine And Public Health, 2018)
Background: Injection is considered as one of the key procedures of drug delivery all over the world. Unsafe injection practices are very common in countries like India. This study was aimed to assess knowledge, attitude and practice of injection safety in a tertiary care hospital of Tripura. Methods: A cross-sectional study was conducted among 300 participants including staff nurses, operation theater (OT) assistants and laboratory technicians of Tripura Medical College and Dr. BRAM Teaching Hospital, Hapania; who were primarily involved in routine injection practices related to patient care from January 15th to February 14th 2018. Data was collected using a self-administered questionnaire and analyzed using SPSS version 16.0. Results: Majority (77%) of the participants in this study belonged to 18 to 25 years age group and were females (71.3%); mostly were nurses (88%), followed by OT assistants (6.3%) and laboratory technicians (5.7%) respectively. Good injection safety practices were reported by majority of the participants (67.3%). Higher mean age with knowledge of injection safety, nurses as compared to others and probational work experience than permanent were found to have significant association with safe injection practices of the participants. Conclusions: Even though study findings showed good practice related to injection safety among the health care personnel like similar other studies in this country, still improvement is required to fulfil the gap in knowledge and attitude of the health care providers to keep unsafe injection to the minimum level.